Thermal processing of fresh concrete with infrared radiation - Alexander P. Svintsov; Alimu Cisse (Structural Mechanics of Engineering Constructions and Buildings, 2021)
Currently, the construction of buildings made of monolithic concrete and reinforced concrete is becoming increasingly relevant. The use of innovative technologies, minimum construction time, durability, reliability, the ability to perform work in various climatic conditions, architectural individuality contribute to the development of monolithic construction. Concrete and reinforced concrete are the main materials of modern construction. The quality of structures depends not only on the composition of concrete, the amount of portland cement, the chemical additives used, the water-cement ratio, the quality of fillers, etc., but also significantly on the heat and humidity regime of concrete holding. To ensure the necessary temperature conditions for hardening and strength gain of concrete, various methods of heating structures are used. One of the methods of concrete care is thermal processing during the hardening period and the acquisition of critical or design strength. The aim of the study is to improve the technology of erection of monolithic concrete and reinforced concrete structures using thermal processing of concrete by means of infrared radiation. The technology of thermal processing of the laid and compacted concrete mixture using infrared heating and a two-chamber transparent shelter for infrared rays has been developed. The obtained results permit us to provide conditions for the normal course of the chemical reaction of hydration, hardening and strength gain. This allows successfully solve the problems of concreting in the erection of buildings and structures made of monolithic concrete and reinforced concrete.